Multidiciplinary Review on The Effects of Backdoor Listing Action Against Standby Purchaser (Acquisitor Company) - Adityadarma Bagus Priasmoro Suryono Putro; Budi Santoso; Rachmi Sulistyarini (Faculty of Law, Universitas Jenderal Soedirman, 2020)
Backdoor Listing is a